1977
DOI: 10.1111/1523-1747.ep12687967
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Hyphae in Cultures of Pityrosporum by Cholesterol and Cholesterol Esters

Abstract: The effect of cholesterol and cholesterol esters on Pityrosporum cultures has been studied. A mixture of 0.25% to 2.0% of cholesterol:cholesteryl stearate:glyceryl monostearate (2.0:1.5:2.0) added to Bacto Yeast Morphology Agar plus oleic acid was able to induce hyphae in cultures of both Pityrosporum orbiculare and P. ovale. This result is discussed with respect to the cholesterol effect on cell membranes and to the occurrence of cholesterol and cholesterol esters in the scaling patches of Pityriasis versicol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…As demonstrated by the control noninoculated CSSS, the underneath face of CSSS which is offered to Malassezia growth in the bioassay is normally free of these yeasts. It has been previously shown that these fungi can grow after inoculation on lipid-enriched human stratum corneum [36,37,40]. We presently confirm this feature and the potent anti-Malassezia activity of topically applied ketoconazole.…”
Section: Discussionsupporting
confidence: 85%
“…As demonstrated by the control noninoculated CSSS, the underneath face of CSSS which is offered to Malassezia growth in the bioassay is normally free of these yeasts. It has been previously shown that these fungi can grow after inoculation on lipid-enriched human stratum corneum [36,37,40]. We presently confirm this feature and the potent anti-Malassezia activity of topically applied ketoconazole.…”
Section: Discussionsupporting
confidence: 85%
“…In vitro , the addition of glucose or asparagine to the culture medium promotes growth of the yeast 59 . Cholesterol and cholesterol esters added to culture also stimulate the induction of hyphae 61 …”
Section: Immune Response To Malassezia In Pityriasis Versicolormentioning
confidence: 99%
“…It was also noted that some of media components can stimulate in vitro the formation of mycelium by Malassezia sp ., for example Porro et al . obtained the growth of Malassezia sp . hyphal by adding cholesterol and cholesterol esters to the medium.…”
Section: Discussionmentioning
confidence: 99%